Comparative efficacy and safety of antiplatelet or anticoagulant therapy in patients with chronic coronary syndromes after percutaneous coronary intervention: A network meta-analysis of randomized controlled trials - Lin, Yaowang; Cai, Zhigang; Dong, Shaohong; Liu, Huadong; Pang, Xinli; Chen, Qiuling; Yuan, Jie; Geng, Qingshan (Frontiers in Pharmacology, 2022)
Aimed to evaluate and compare the interactive effects of different antiplatelet or anticoagulation strategies in patients with CCS after PCI. Randomized controlled trials comparing different antiplatelet or anticoagulant strategies in patients with CCS after PCI were included. The primary outcomes were major adverse cardiovascular event (MACE), mortality, ischemic and bleeding events. Compared to aspirin alone, addition of prasugrel or ticagrelor to aspirin resulted in lower risk of myocardial infarction (MI) [odds ratio (OR): 0.38 (95% confidence interval 0.38–0.62); 0.810–0.84 (0.69–0.98)] and any stroke [0.56 (0.42–0.75)] at the expense of increased risk of major bleeding [1.79 (1.34–2.39); 2.08–2.38 (1.56–3.28)], whereas, clopidogrel monotherapy reduced the risk of any stroke, major bleeding, and intracranial bleeding. On subgroup analysis, compared with aspirin alone, addition of prasugrel resulted in lower MACE [0.72 (0.60–0.86)], MI [0.48 (0.38–0.62)] and stent thrombosis [0.29 (0.09–0.91)], whereas, addition of rivaroxaban 2.5 mg resulted in lower risk of MACE [0.72 (0.60–0.87)], cardiac death [0.71 (0.52–0.98)] and any stroke [0.65 (0.45–0.95)], but not reduced MI. Both prasugrel and rivaroxaban 2.5 mg increased major bleeding [1.79 (1.34–2.39); 1.72 (1.33–2.22)]. Clopidogrel monotherapy was associated with lower MACE [0.72 (0.58–0.90)], any stroke [0.42 (0.24–0.73)], and major bleeding [0.62 (0.40–0.96)]. Adding prasugrel or ticagrelor led to a reduced incidence of MI and prasugrel was also found to reduce the risk of MACE and stent thrombosis in CCS patients with low risk of bleeding after PCI. Clopidogrel monotherapy has advantage in reducing MACE, stroke, and major bleeding events in CCS patients at high risk of bleeding after PCI.